Analisis Putusan Mahkamah Agung Terhadap Perkara Wanprestasi Pembangunan Perumahan: (Studi Kasus Perkara Nomor 694/PK/Pdt/2017) - Ida Ayu Anom Tri Laksmi; Aris Munandar (Private Law, 2023)
The aim of this research is to find out the Judge’s consideration basis in resolving the default case of house construction contracts, case number 694/PK/Pdt/2017 along with its legal consequences. Applied research method in normative-juridical and doctrinal legal research. Research result indicates that (1) The Judge’s consideration basis in resolving default case number 694/PK/Pdt/2017 are previous Judges' verdict and regulation on default; (2) Emerging legal consequences from this default case is the contract is legally voidable and appeal pleader obliged to compensate defendant’s loss, also obliged to pay for interest and trial fee.